TIMECOURSE OF SYNAPSE DEVELOPMENT IN HUMAN IPSC-DERIVED NEURONS - Orbita, Adrienne Marie (East Carolina University, 2019)
Understanding the underlying mechanisms in brain formation give an insight to what affects the formation of the brain when affected with autism, specifically, the excitatory and inhibitory synapses. The mechanism of how it is regulated in the brain is important because it shows the inherent development of the brain when affected with a neurodegenerative disease. The studying of these synapses also give light to any disruption of function in the brains affected with autism. Autism is associated with affecting the regions of the brain that control social interaction, communication, and their reasoning. As autism prevalence rises, there is a greater need to understand these mechanisms to boost the knowledge than can be used for further research. To make this a feasible task, human induced pluripotent stem cells (hIPSC) are used to conduct these experiments. This allows for a model that can develop both excitatory and inhibitory synapses that can recapitulate synapse development and gather insight on the 3-D and 2-D models created. In this experiment, the motion of decreased inhibitory synapses will result in an increase of excitatory synapse formation in 3-D models. In 2-D models, synapse area will increase with the increase in neurite length and density over time. The result from these various experiments contribute to a greater understanding to the mechanisms of these synapses and show the relationship of how important these are to the development of the human brain. The project also supports the future directions of using data from this experiment to observe drug studies that may include ROCK inhibitors and previous research to be able to observe further development of the stem cells.
Keywords: autism, hIPSC, synapses